Wear properties of coated and uncoated glass and basalt fibre reinforced polyester composites - Yusof, F. M.; Jumahat, A.; Zahib, Z. M.; Rahman, N. L. A.; Maslan, A. A.; Chalid, M. (UiTM Press, 2025)
This research investigates the tribological behavior of polytetrafluoroethylene (PTFE) coated and uncoated synthetic glass fiber (GF) and basalt fiber (BF) polyester composites. It aims to enhance the wear resistance of GF and BF composites by applying a PTFE coating. The presence of thermoplastic coating is designed to improve the GF and BF composites durability and functionality, hence reducing maintenance costs by minimizing wear and tear. Physical and tribological tests were conducted, including sliding wear and abrasion tests to assess dry particle abrasive wear resistance, and also a pin-ondisk test to evaluate the coefficient of friction and roughness/smoothness of the materials surface. The tribological performance of the fibre reinforced polymer (FRP) composites with and without PTFE coatings was compared. The findings revealed that the Glass Fiber Reinforced Polymer (GFRP) composite exhibited the highest density, while the PTFE-coated Basalt Fiber Reinforced Polymer (BFRP) composite had the lowest density, with the PTFE-coated GFRP falling in between. In sliding abrasion tests, GFRP had a higher wear volume than BFRP, which demonstrated a 66% reduction in wear volume due to its superior hardness. PTFE-coated BFRP showed the lowest specific wear rate, decreasing by 56% compared to GFRP, which had the highest rate. In the dry particle abrasion test, PTFE-coated GFRP exhibited the lowest wear volume, reducing by 57% compared to BFRP. Overall, the study demonstrates that PTFE coatings significantly enhance the wear resistance and tribological performance of fiber-reinforced polymer composites. Hence, this will extend their lifespan and reduce the maintenance costs of the FRP structure.